Tanggungjawab Orang Tua terhadap Pendidikan Anak Usia Dini Perspektif Hadis - Usman, Usman; Syafri, Edi; Rehani, Rehani; Tamrin, Muhammad Isnando; Zalkhairi, Zalkhairi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2021)
This study aims to describe the responsibilities of parents towards children's education at an early age by using a hadith perspective. Parents who are in charge of education have a very dominant role in the process of children's education. Parents and children have an emotional relationship and intensive educative inter action, this can be a positive educational atmosphere. This article is a theoretical study by using data sources from library searches in the form of books and journal articles related to the formulation of the problem. The approach used is an educative approach, which examines the responsibility of parents to children's education at an early age in the perspective of hadith by using qualitative data analysis methods. The research findings are parents as the party who is in the first order responsible for their children's education. The responsibility of parents regarding education concerns the good of the child in this world and the hereafter. The responsibility for children's education has been prepared long before the child is born. In this research there are nine forms of parental responsibility for the education of children at an early age.